Total Harmonic Distortion Analysis of a Four Switch 3-Phase Inverter Fed Speed Sensorless Control of IM Drives - Zakaria M.S. El-Barbary; H. Z. Azazi; M. K. Metwally (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This paper investigates the performance of a Model reference adaptive system (MRAS) based cost-effective drive system of an induction motor (IM) for low-cost applications - high performance industrial drive systems . In this paper, the MRAS is used as a speed estimator and the motor is fed from a four-switch three-phase (FSTP) inverter instead of a conventional six-switch three-phase (SSTP) inverter. This configuration reduces the cost of the inverter, the switching losses, and the complexity of the control algorithms and interface circuits, the proposed control approach reduces the computation for real-time implementation.. The robustness of the proposed MRAS-based FSTP inverter fed IM drive is verified by Experimental results at different operating conditions using digital signal processor (DSP1103) for a 1.1 Kw motor. A performance comparison of the proposed FSTP inverter fed IM drive with a conventional SSTP inverter system is also made in terms of speed response and total harmonic distortion (THD) of the stator current. The proposed FSTP inverter fed IM drive is found quite acceptable considering its performance, cost reduction and other advantages features.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.5036